Aplikasi Fuzzy Berbasis Web untuk Rekomendasi Pemilihan Universitas Swasta (Fuzzy-Based Web Application - Lasmedi Afuan; Ipung Permadi (JUITA : Jurnal Informatika, 2011)
Development of computer technology today has been change rapidly. Choosing the university is very important for student. One of student problem choosing university is available many universities which can make confusing the student. Aware how important choosing best university. So, must be planning a application program at education sector in particular fuzzy application for decision support choosing university based web. This fuzzy application build using fuzzy variable such as faculty,majors, accreditation, number of lectures, infrastructures, etc. Application web by using internet media be intended can accessed by all of people and help student take decision for choosing  the best university